2016
DOI: 10.1016/j.rmed.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bronchiectasis in the elderly

Abstract: Bronchiectasis does not substantially differ across age groups. Poor outcomes in elderly patients with bronchiectasis might be directly related to individual's frailty that should be further investigated in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…Collaborators from EMBARC have also published data demonstrating the characteristics of bronchiectasis in the elderly [ 30 ], demonstrating that only a minority of bronchiectasis patients are represented in current randomised clinical trials, such as those of inhaled antibiotics and mucoactive therapies [ 31 ].…”
Section: Achievements Of Embarcmentioning
confidence: 99%
“…Collaborators from EMBARC have also published data demonstrating the characteristics of bronchiectasis in the elderly [ 30 ], demonstrating that only a minority of bronchiectasis patients are represented in current randomised clinical trials, such as those of inhaled antibiotics and mucoactive therapies [ 31 ].…”
Section: Achievements Of Embarcmentioning
confidence: 99%
“…In one study of over 1,200 patients with bronchiectasis, 50% were over 65 years old and 19.1% were over 75 years. 2 Increasing age is recognized as an independent risk factor for bronchiectasis severity. 3 , 4 Other markers of generalized frailty in the elderly population such as impaired forced expiratory volume in 1 second (FEV 1 ), low body mass index (BMI) and recent hospitalization also impact on the disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that this pathology is more frequent in women and older individuals and many patients tend to have a more severe and symptomatic disease. Bellelli G et al reported in one study of over 1,200 patients with bronchiectasis, 50% were over 65 years old and 19.1% were over 75 years (9). Increasing age is recognized as an independent risk factor for bronchiectasis severity (10).…”
Section: Prevalencementioning
confidence: 99%